Norwegian reference values for the Short Physical Performance Battery (SPPB): the Tromsø Study - Bergland, Astrid (BMC Geriatr, 2019)
BACKGROUND: The Short Physical Performance Battery (SPPB) is a common well-established instrument to measure physical performance. It involves a timed 4-m walk, timed repeated chair sit-to-stand test, and 10-s balance tests (side-by-side, semi-tandem, and full-tandem). We aimed to establish reference values for community-dwelling Norwegian adults aged 40 years or older in terms of (1) the total score; (2) the three subtest scores; and (3) the time to complete the repeated chair sit-to-stand test and the walking speed. Additionally, we explored floor and ceiling effects for the SPPB. METHODS: The study population comprised home dwellers aged 40 years or more who participated in the 7th wave of the Tromsø study. A sample of 7474 participants (53.2% women) completed the SPPB. Crude mean values and standard deviations (SD) were evaluated according to sex and age group. Mean values at specific ages were then estimated using linear regression, along with corresponding 95% confidence intervals. Additionally, quantile regression was used to estimate age-specific percentiles (5th, 10th, 25th, 50th, 75th, 90th, and 95th percentiles). RESULTS: Considerable variability in SPPB scores was observed. The mean SPPB total score of the entire sample was 11.4 (SD 1.3) points. On average, the SPPB total score was 0.28 points greater in men than in women (p < 0.001). Significant sex differences were observed in all five age groups (40–49, 50–59, 60–69, 70–74, 75–79, and 80+ years). The main decline in the physical function occurred in the mid-sixties, with a slightly earlier decline in women than in men. Ceiling effects were observed in all age groups. CONCLUSIONS: The present study provides comprehensive, up-to-date normative values for SPPB measures in community-dwelling Norwegians aged at least 40 years that may be used to interpret the results of studies evaluating and establishing appropriate treatment goals. Because of ceiling effects, the SPPB has important limitations for the assessment of physical functioning across the full spectrum of the community-dwelling adults aged 40+ years. Furthermore, we conclude that performance on the SPPB should be reported in terms of the total sum score and registered time to complete the repeated chair sit-to stand test and timed 4-m walk test.